(untitled) (The Pakistan Development Review, 1999)
Cultural change and social transformation are essential elements of the process of development. They complement and sustain economic growth. Economic historians acknowledge that the rise of the West from poverty to wealth was as much the result of improvements in trade, savings, investment and productivity as of emerging norms of thrift, trust, specialisation, rationality and contractual relations [Rosenberg and Birdzell (1986)]. In fact, it would not be an exaggeration to say that economic development is essentially a phenomenon of cultural change. The recognition of the role of cultural and social factors in economic growth has led to a subtle revision of the terminology from ‘economic development’ to the adjectiveless term ‘development’ or the fully spelled out title of economic and social development. Yet this acknowledgement has remained largely on the conceptual plane. It has not been translated into policies and programmes to deliberately set the direction of cultural change and define the alignment of social organisation. Development strategies have, by and large, treated social and cultural factors as exogenous variables. This is true of development planning in general and in particular of its practice in Pakistan. In fifty years of economic planning in Pakistan, little attention has been paid to the social and cultural aspects of development.